2002
DOI: 10.1007/s005350200130
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of Helicobacter pylori eradication in Mongolian gerbils

Abstract: These results suggest that H. pylori eradication may have had a therapeutic effect not only on gastritis, erosion, and gastric ulcer but also on glandular atrophy, intestinal metaplasia, and gastric carcinoid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Yamagata Prefecture therefore has attempted aggressively to achieve secondary prevention of gastric cancer. In 1994, IARC/WHO concluded that Helicobacter pylori (H pylori) is a definite carcinogen in humans [2] , and the results of a prospective cohort study [3] and animal studies [4][5][6] have demonstrated that H pylori causes gastric cancer. The possible role of H pylori eradication therapy in primary prevention of gastric cancer has thus attracted substantial interest in Yamagata Prefecture.…”
Section: Introductionmentioning
confidence: 99%
“…Yamagata Prefecture therefore has attempted aggressively to achieve secondary prevention of gastric cancer. In 1994, IARC/WHO concluded that Helicobacter pylori (H pylori) is a definite carcinogen in humans [2] , and the results of a prospective cohort study [3] and animal studies [4][5][6] have demonstrated that H pylori causes gastric cancer. The possible role of H pylori eradication therapy in primary prevention of gastric cancer has thus attracted substantial interest in Yamagata Prefecture.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to evaluate GIM, which is generally thought to be a precancerous condition in gastric cancer (12,18). Furthermore, a previous study has shown that GIM is closely associated with Helicobacter pylori infection (31). However, little is known about the genetic events responsible for initiation and progression of gastric cancer (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…However, molecular markers have not been thoroughly explored with regard to the pathogenesis of the lesions in gerbils, and longer follow-up is now necessary to confirm the long-term benefit of eradication treatment. 31) This work was supported in part by a Grant-in-Aid for Cancer Research from the Ministry of Health, Labour and Welfare, Japan, and a Grant-in-Aid from the Ministry of Education, Culture, Sports, Science and Technology of Japan. X.C.…”
Section: Discussionmentioning
confidence: 99%